MORPHOLOGICAL PECULIARITIES OF BLOOD SUPPLY OF THE PINEAL BODY DEPENDING ON ITS LOCALIZATION IN THE HEAD BRAIN OF RATS - Пшиченко, В.В.; Cherno, V.S. (World of Medicine and Biology, 2018)
In an experiment on 24 sexually mature males, the Wistar lines of rats that were kept in standard vivarium conditions studied the features of the blood supply of the pineal body, depending on its location in the brain in rats. As a result of our macroscopic study, the localization of the pineal body in the brain in rats has certain individual variations. In some cases, the tip of the organ, that is, its smallest part, is clearly visualized in the furrow between the posterior edges of the occipital particles of the cerebral hemispheres in the form of a spherical form of light-gray color formation. Almost no distinctive guideline of boundaries in this case is the presence of blood vessels that closely adhere to the pineal-like body and surround it. These vascular plexus are a direct extension of the vascular layer III of the ventricle of the brain. Often these vascular plexuses penetrate into the pineal body. There are variants in which the apical part of the pineal-shaped body does not appear between the hemispheres of the brain in the area of the occipital particles. In this case, the pineal body can be detected between the tubercles of the corpora quadrigemina, in the furrow between them. To detect it, it is necessary to lower the cerebellum and raise the occipital particle of the hemispheres. Thus between the top of the quadrigemina visible pineal body. n some cases, it appears to be connected to the lower surface of the cerebral hemisphere by means of a plate of soft cerebellum. With such a localization of the pineal gland, as a rule, there is no close connection with the vascular plexus. On its surface differ only in some blood vessels surrounding and tightly adjacent to the pineal body. At the macroscopic level, in the preparation of the pineal-like body of experimental animals, in most cases, we found that it was closely related to the vascular plexus, located under the cover and on the walls of the ІІІ ventricle of the brain. This plexus is so tightly supplemented with a pineal body that separates it from the body is impossible without damage to it. In the event that the operation to separate the pineal body from the vascular plexus still manages, the perforation apertures are determined in the upper part of the organ, which are clearly detected on the histological sections, made in the corresponding plane. If the slices are made in the plane perpendicular to the course of the blood vessels, the perforation holes have a rounded shape with fairly distinct edges. When making a cut, at any angle to the direction of the circulation of the blood vessel, the perforation aperture changes its shape from the oval to the oblong. It is revealed that there are other forms of the relationship between these anatomical structures. In the latter case, one, maximum of two isolated blood vessels, which branch out, penetrate the body, approaches to the pineal-shaped body. It was established that the source of blood supply to the pineal body and in this case is vascular plexus, located under the cover of the III ventricle of the brain. The results of our study on the topography of the pineal gland in laboratory rats agree with the results of research R.J. Reiter [15] and J. Arendit [7] and show that the location of the pineal body in the brain of individual individuals has individual characteristics.